Upaya Peningkatan Kinerja Mandor dan Supervisor pada Departemen EBM, IMM, dan AD di PT. X - Devon Antonio Saputra; Felecia Felecia (Jurnal Titra, 2022)
PT. X is a company engaged in cosmetic plastic packaging products such as bottles, jars, powder packaging, lipstick packaging, etc. PT. X wants to increase the number of to be produced per man hour (TBP/MH) which was initially Rp. 170,000.00, to reach the target of Rp. 230,000.00 by increasing production leaders’ performance, namely the shift leaders and supervisors. This is because there are still many inputs about production problems that are not being watched by production leaders, causing production output not reaching TBP/MH target. This study uses the day in the life of (DILO) method to categorize and sort the daily activities of the shift leaders and supervisors. The results obtained are the shift leaders and supervisors are less in control of operators, and the number of non-value-added activities is greater than the value-added activities. This study proposed several daily schedules that have been adapted to the company's job description and increasing the time for value-added activities by eliminating non-value-added activities. This is done because the activities of the shift leaders and supervisors support operators and their production output, which also make return to the company's TBP/MH number. If proposed schedules are implemented, it will increase the value-added activity time by 18.79% to 44.03%.